Selective tissue elevation by pressure for endoscopic mucosal resection of colorectal adenoma: first clinical trial - Belle, Sebastian; Ströbel, Philipp; Post, Stefan; Kähler, Georg (Surgical endoscopy and other interventional techniques, 2012)
Background: Endoscopic mucosal resection (EMR) and endoscopic submucosal dissection of large lateral spreading tumors currently are technically limited by complications such as bleeding, perforation, and disturbed large procedural sites, leading to incomplete resection and secondary surgery. Further technical improvements are necessary. The authors previously demonstrated the effectiveness of a focused water jet for elevation of the lamina submucosa in animal studies. For the first time, the clinical application of selective tissue elevation by pressure (STEP) for the treatment of colorectal adenomas as a prospective single-arm human trial is presented.MethodsThis trial evaluated 59 patients who had primary colorectal adenomas with diameters exceeding 12 mm classified as 0-IIa or 0-IIb according to Paris classification. A submucosal cushion was created with a flexible water jet applicator using the Helix HydroJet. The adenoma was subsequently resected with a mucosal resection snare. All results were recorded. The resected specimens were assessed histologically.ResultsA total of 59 patients underwent resection of 70 lesions with a maximum diameter of 80 mm (mean, 27 mm). Submucosal elevation with the water jet dissector was possible in all cases and locations from the pectinate line to the ileocecal valve. Of the 70 lesions, 64 (91%) were resected completely in one session. Histologically, the resected specimens were found to be adenocarcinomas (n = 2, 3%), adenomas with high-grade intraepithelial neoplasia (n = 24, 34%), adenomas with low-grade intraepithelial neoplasia (n = 38, 54%), and hyperplastic polyps (n = 6, 9%). Hemostasis during the resection was necessary in 24 cases (34%). No perforation required surgical intervention.ConclusionThis first clinical trial to analyze STEP technique demonstrated that STEP used to elevate large mucosal lesions in any location is feasible and facilitates EMR for colorectal adenoma.
Gesehen am 13.07.2018
Published online: 13 October 2011